Host status of melon, carrot, and Meloidogyne incognita-susceptible and -resistant cotton, cowpea, pepper, and tomato for M. floridensis from California - Ploeg Antoon T.; Edwards Scott (Journal of Nematology)
The host status of carrot, melon, and susceptible and resistant cultivars of tomato, cotton, cowpea, and pepper for a California isolate of the peach root-knot nematode Meloidogyne floridensis was determined in greenhouse pot experiments. It was compared to a race 3 isolate of M. incognita. Melon was an excellent host for both isolates and roots were heavily galled after the 8-week trial. Carrot was a host for M. incognita, but a poor host for M. floridensis, although both isolates caused similar levels of galling. Susceptible cotton was a good host for M. incognita race 3, but a poor host for M. floridensis. Susceptible tomato, cowpea, and pepper were good hosts for both isolates. The M. incognita resistance in tomato and pepper was broken by M. floridensis. Resistant cowpea was a maintenance host as population levels of M. floridensis remained virtually unchanged over the trial period. We conclude that M. floridensis poses a risk to some important vegetable crops in California, as it reproduces on most vegetable crops, including some cultivars that are resistant to M. incognita. On susceptible crops, the reproduction of M. floridensis was always significantly less than that of M. incognita, and we hypothesize that in mixed species field populations, M. incognita will outcompete M. floridensis. This study demonstrates that efforts to limit the spread and prevent further introductions of M. floridensis in California are important to maintain the effectiveness of plant resistance as a nematode management strategy in vegetable crops.